Implementation of Augmented Reality-Based Promotional Application for Traditional Food at Cakwe Medan Pak Budi - Haryanto, Haryanto; Fridayanthie, Eka W; Firdaus, Maulana; Budiman, Alwi; Susila, Mochamad Nandi (Jurnal Multidisiplin Sahombu, 2025)
Technological advances have had a major influence on the field of information and communication technology. There are several ways to recognize technical progress in the food sector. Today, food stores offer more than just food to every visitor or client. When opposed to eating at home, the store is the place to look for the variety of foods it offers. Each store will be able to provide something unique, which presents a problem for store owners who must constantly contend with intense competition. This is very important because Toko Cakwe Medan must be able to provide food quickly to satisfy every guest/customer. The Fast Corner algorithm is Edward Rosten's approach used to determine corner points after the image is converted to black and white. The approach that uses corner point determination techniques begins by identifying a point p from the input image. The 16 pixels adjacent to p are then verified. Fast Corner Detection excludes a significant percentage of non-corners by utilizing a high-speed type of Fast Corner Detection in its implementation. This research displays products in 3D. From this analysis, it was identified that the scanned product was an interesting promotional idea to attract Jadoel food enthusiasts, create attractive promotional media, and a food product that could satisfy customers who wanted to buy.